2017
DOI: 10.1002/ece3.3453
|View full text |Cite
|
Sign up to set email alerts
|

Prozac in the water: Chronic fluoxetine exposure and predation risk interact to shape behaviors in an estuarine crab

Abstract: Predators exert considerable top‐down pressure on ecosystems by directly consuming prey or indirectly influencing their foraging behaviors and habitat use. Prey is, therefore, forced to balance predation risk with resource reward. A growing list of anthropogenic stressors such as rising temperatures and ocean acidification has been shown to influence prey risk behaviors and subsequently alter important ecosystem processes. Yet, limited attention has been paid to the effects of chronic pharmaceutical exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 64 publications
0
8
1
Order By: Relevance
“…However, boldness in crucian carp was only affected by High FLX and not by Low FLX, the concentration that fish may encounter in the wild. This is in contrast to earlier studies where, for example, crabs reared in presence of a predator showed an increase in foraging and activity along with a more aggressive personality style when exposed to environmentally relevant concentrations of FLX (Peters et al., 2017). However, bioaccumulation of FLX differs between taxa (Boström et al., 2017; Lagesson et al., 2016) and drug targets and affinity may also vary, making the read‐across hypothesis less applicable outside its intended domain.…”
Section: Discussioncontrasting
confidence: 99%
“…However, boldness in crucian carp was only affected by High FLX and not by Low FLX, the concentration that fish may encounter in the wild. This is in contrast to earlier studies where, for example, crabs reared in presence of a predator showed an increase in foraging and activity along with a more aggressive personality style when exposed to environmentally relevant concentrations of FLX (Peters et al., 2017). However, bioaccumulation of FLX differs between taxa (Boström et al., 2017; Lagesson et al., 2016) and drug targets and affinity may also vary, making the read‐across hypothesis less applicable outside its intended domain.…”
Section: Discussioncontrasting
confidence: 99%
“…The primary target molecule of fluoxetine (the serotonin transport molecule) is conserved across all vertebrate taxa [7], and, thus, fluoxetine has the potential to affect a diverse array of ecologically important behaviours in wildlife [8,9]. Indeed, there is growing evidence that antidepressants, such as fluoxetine, can disrupt a range of behaviours in non-target species at environmentally relevant concentrations, such as activity [10][11][12][13], anxiety [14][15][16], predator avoidance and escape [17][18][19][20], and foraging [21,22]. However, to date, few studies have considered how impacts of psychoactive pollutants might be affected by social context [23,24], and fewer still have directly asked whether impacts seen in social isolation are reflective of those in a social context [25].…”
Section: Introductionmentioning
confidence: 99%
“…The use of medicines may result in leftovers, and the absence of information from the population about how to proceed with these pharmaceutical products wastes can cause risks to the environment and human been (4)(5)(6). Many drugs have compounds with high potential for bioaccumulation and low biodegradability, and when deposited in the environment, can contaminate soil and water and cause effects on aquatic animals (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Some classes of drugs present greater relevance for environmental contamination by interfering directly in living systems, such as antibiotics and endocrine disruptors (6)(7)(8)(9). Aditya and Rattan (2014) and Pinto and cols (2014) showed a predominance in the inadequate disposal of antibiotics, and the bacterial resistance is the major concern regarding the disposal of this pharmacological class (10,11).…”
Section: Introductionmentioning
confidence: 99%